2018
DOI: 10.1093/annonc/mdx726
|View full text |Cite
|
Sign up to set email alerts
|

Impact of neoadjuvant chemoradiotherapy on health-related quality of life in long-term survivors of esophageal or junctional cancer: results from the randomized CROSS trial

Abstract: Netherlands Trial Register NTR487.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 21 publications
6
62
1
5
Order By: Relevance
“…HRQoL data from the CROSS trial, which compared surgery alone with nCRT followed by surgery, were reported recently. There was no difference in HRQoL between the treatment groups, even in the long term. Possible explanations for the discrepancy between these findings and those of the present study could be that subtle effects of the neoadjuvant treatment itself may have been masked by the massive effects of surgery on HRQoL in both studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…HRQoL data from the CROSS trial, which compared surgery alone with nCRT followed by surgery, were reported recently. There was no difference in HRQoL between the treatment groups, even in the long term. Possible explanations for the discrepancy between these findings and those of the present study could be that subtle effects of the neoadjuvant treatment itself may have been masked by the massive effects of surgery on HRQoL in both studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, the methodology of the studies differed slightly. The present study focused on direct comparison of the two treatments as opposed to longitudinal comparisons with baseline in the CROSS study. Longitudinal comparisons with baseline have the advantage of better statistical power than the direct arm‐to‐arm comparisons at 5 years' follow‐up.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon has been described to a lesser extent in patients with prostate cancer 16,33 . The high postoperative morbidity and mortality rates associated with oesophagectomy, and the lasting impact of such surgery on patients' HRQoL likely underlie the substantial loss of life expectancy that patients are willing to trade off 3,11,12 . For clinicians, who tend to focus on long-term survival outcomes, it is important to realize that patients and physicians may differ in their trade-offs between different treatment options 15 -17,25,34,35 . The present findings may help patients and clinicians choose between active surveillance and oesophagectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Relevant attributes that might influence the choice of oesophagectomy versus active surveillance after nCRT and the attribute levels were chosen based on information in the literature, and consensus discussion with two upper gastrointestinal surgeons and five patients who underwent nCRT followed by surgical resection. Attributes were 5‐year overall survival, short‐term HRQoL (3 months after treatment), long‐term HRQoL (more than 1 year after treatment), the risk that oesophagectomy is still necessary, and the average number of surveillance examinations per year involving endoscopy and PET–CT necessary for 5 years of follow‐up after treatment ( Table ).…”
Section: Methodsmentioning
confidence: 99%
“…However, the ARTIST (Adjuvant Chemoradiation Therapy in Stomach Cancer) trial [23] found that additional postoperative radiotherapy had the same bene t as chemotherapy alone in preventing recurrence of gastric cancer. Therefore, while focusing on randomized clinical trials [24,25], we also need to develop and optimize treatment strategies that accord with the medical conditions of the local area.We found that stage III AEG mainly metastasizes to distant sites, predominantly through hematogenous transmission. We recommend increasing the number of follow-up visits within 2 years after surgery, especially in the second year.…”
Section: Site Of Tumor Recurrencementioning
confidence: 99%